2022
DOI: 10.37905/aksara.8.3.2397-2408.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sunbathing as Caring for Covid-19 Patients: A Literature Review

Abstract: COVID-19 adalah penyakit baru yang muncul kritis karena disebut sebagai penyakit coronavirus baru dan menambah beban penyakit secara global. Penelitian ini bertujuan untuk mengetahui literatur mengenai efektivitas berjemur pada pasien COVID-19. Analisis artikel penelitian dan teori keperawatan dilakukan untuk mensintesis konsep. Temuan tersebut mengungkapkan bahwa meskipun peran sinar matahari sebagai faktor pelindung untuk COVID-19 masih kontradiktif, namun, teori keperawatan dan berbagai penelitian terbaru b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…35 Vitamin D modulates both innate and adaptive immune systems. 24,25,36 There was no significant relationship between gender and the presence of symptoms in COVID-19 patients. Although women in their reproductive period are benefitted from the presence of estrogen, which helps the immune system 30 , however, in this study, both men and women showed no different results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…35 Vitamin D modulates both innate and adaptive immune systems. 24,25,36 There was no significant relationship between gender and the presence of symptoms in COVID-19 patients. Although women in their reproductive period are benefitted from the presence of estrogen, which helps the immune system 30 , however, in this study, both men and women showed no different results.…”
Section: Discussionmentioning
confidence: 83%
“…Many health facilities such as hospitals provide sunbathing therapy to get additional vitamin D and reduce the symptoms felt by COVID-19 patients. 25,26 Since vitamin D is known to play a role in increasing the activity of the immune system, however it is still controversial whether Indonesians who are living in the tropical zone will be more resistant to infectious diseases than other people living in sub-tropical countries. This is showed by the increase in morbidity and mortality due to COVID-19 is still occurring in Indonesia, even though countries with temperate climates still report higher disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, pendampingan juga dilakukan dalam bentuk mengingatkan para santri tentang manfaat berjemur di pagi hari untuk meningkatkan imunitas tubuh. Berdasarkan berbagai hasil penelitian, mengonsumsi vitamin (terutama vitamin C dan vitamin D) serta berjemur dapat meningkatkan imunitas tubuh, terutama di masa pandemi Covid-19, sehingga tidak mudah tertular (Aisy, Rizal, & Simanjuntak, 2023;Cicero, Fogacci, & Borghi, 2022;Saluy, Langingi, & Kaparang, 2022;Sudibjo et al, 2021) Gambar 3. Edukasi Hidup Sehat Dan Minum Vitamin…”
Section: Mencuci Tangan Dengan Sabununclassified
“…Recent results suggest that vitamin D can prevent infection with COVID-19 pandemic 11 . Ultraviolet B rays from sunlight have also been proven to enhance the healing of patients 12 . Vitamin D is reported to have many effects on the immune system, including the ability [33][34][35][36][37][38][39] to enhance the function of macrophages, and neutrophils, as well as to activate T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Information about the importance of vitamin D in preventing the pandemic has spread widely to the public. Therefore, many healthcare facilities recommend sun exposure to obtain additional vitamin D and reduce symptoms experienced by patients 12,16 . This study warrants further exploration to determine whether vitamin D enhances the immune system.…”
Section: Introductionmentioning
confidence: 99%